Diffusion imaging changes in the treated tract following focused ultrasound thalamotomy for tremor - Erin L. Mazerolle; Robyn Warwaruk-Rogers; Paul Romo; Tejas Sankar; Sarah Scott; Conrad P. Rockel; Samuel Pichardo; Davide Martino; Zelma H.T. Kiss; G. Bruce Pike (NeuroImage: Reports)
We describe diffusion tensor imaging metrics of brain microstructure changes following magnetic resonance guided focused ultrasound (MRgFUS) ablation of the ventral intermediate nucleus of the thalamus for the treatment of tremor in order to explore the mechanisms of tremor reduction post-MRgFUS. Tractography was performed on pre-treatment images to identify the portion of the dentato-rubro-thalamo-cortical tract (DRTT) intersecting the MRgFUS thalamotomy lesions in 17 essential tremor patients. The resulting tract was divided into regions of interest (ROI), which were then analyzed on pre-, one day post-, and three months post-treatment scans. Fractional anisotropy (FA), and mean, axial, and radial diffusivity (MD, AD, and RD) were computed in each ROI at each time point. At both one day and three months post-treatment, we observed decreased FA and increased MD and RD in the section of the treated tract between the lesion and cortex. At three months post-treatment, we additionally observed increased AD in the section between the lesion and cortex, and decreased FA in the section between the dentate nucleus and the decussation of the superior cerebellar peduncles. Diffusion changes at one day post-treatment may reflect local, acute effects such as inflammation and edema, as opposed to chronic degenerative processes such as axonal degeneration and myelin loss that would be expected at later time points. No significant correlations were detected between diffusion measures and clinical effects, suggesting that microstructural changes in the treated portion of the DRTT alone do not fully explain tremor reduction and motivating additional research using higher spatial resolution diffusion imaging and multimodal approaches such as integrating diffusion and functional magnetic resonance imaging data. Our individualized approach, in which patient-specific lesions are incorporated into the tractography analysis, provided novel insight into both immediate and longer term MRgFUS-related microstructural brain changes.